Visual function and disability are associated with microcystic macular edema, macular and peripapillary vessel density in patients with neuromyelitis optica spectrum disorder - Li, Jin; Chen, Yihong; Zhang, Ying; He, Zhiyong; Yu, Huankai; Shi, Ce; Shen, Meixiao; Lu, Fan (Frontiers in Neurology, 2022)
Purpose To assess macular and peripapillary vessel density and neurodegeneration in eyes with and without microcystic macular edema (MME) in neuromyelitis optica spectrum disorder (NMOSD) patients while investigating their association with visual impairment and disease disability. Methods This is a cross-sectional study. A total of 52 eyes from 29 NMOSD patients were recruited, including 8 eyes with MME from 7 patients. Optical coherence tomography angiography (OCTA) images were analyzed to quantify the radial papillary capillary density (RPCD), and the density of macular microvascular network in both the superficial retinal capillary plexus (SRCP) and the deep retinal capillary plexus (DRCP). Thicknesses of the neural retinal layers centered on the fovea and the optic nerve head were also collected by OCT. Best-corrected visual acuity (BCVA) and Expanded Disability Status Scale (EDSS) scores were assessed for all patients. Microvascular densities and retinal sublayer thicknesses were compared among groups, and correlations of these vascular and structural parameters with BCVA and EDSS scores were determined. Results Patients with NMOSD and MME had significantly decreased visual acuity and worse EDSS score than patients without MME (P = 0.01 and 0.002, respectively). The vessel density in SRCP and RPCD were significantly lower in eyes with MME and ON compared to that of eyes with ON but without MME and eyes without MME or ON. Impairment of visual acuity and disease severity were significantly negatively associated with the reduction of SRCP vessel density and RPCD but were not related to DRCP vessel density. Conclusions MME were correlated with worse visual impairment and disability in NMOSD patients. Sparse SRCP vessel density and RPCD were observed in NMOSD MME eyes and correlated with worse BCVA and EDSS scores.